Scanning Sildenafil Citrate Solubility in Hydrotropic Solutions - Ebtissam Al-dulaimi; Mohanad Alfahad; Mohannad Qazzaz (University of Mosul, 2023)
Background: Sildenafil citrate (SC) is a selective phosphodiesterase-5 inhibitor with low aqueous solubility (4.1 mg/mL in water), resulting in only 40% bioavailability after oral administration. SC is classified as class II by the Biopharmaceutical Drug Classification System. Hydrotropic agents are ionisable organic salts that provide a simple, safe and effective technique for enhancing the solubility of poorly water-soluble drugs. Method: Solubility study of SC was conducted in water (as a reference) and in various hydrotropic solutions separately (including sodium benzoate, sodium acetate, Urea and mannitol). The concentrations of the hydrotropic solutions were at 10, 20 and 30 % solution concentration, as well as in the solution of 30 % concentration of mixed hydrotropic agents at a 1:1 ratio. Results: The results show marked enhancement of SC solubility in solution of urea at different concentrations while the solubility was enhanced only in 30% solution of sodium benzoate and slightly enhanced in 30% mannitol solution and mannitol-urea solution. The solubility enhancement in urea shows a positive relationship with solution concentration. In addition, the SC solubility was reduced in the solution of sodium acetate at all concentrations and in the solution of sodium benzoate at concentrations of both 10 and 20 % as well as in all mixed hydrotropic solution containing these two agents. Conclusion: Urea shows promising data as a potential additive with SC to achieve higher solubility and bioavailability of the compound.The results show marked enhancement of SC solubility in solution of urea at different concentrations while the solubility was enhanced only in 30% solution of sodium benzoate and slightly enhanced in 30% mannitol solution and mannitol-urea solution. The solubility enhancement in urea shows a positive relationship with solution concentration.In addition, the SC was reduced in the solution of sodium acetate at all concentrations and in the solution of sodium benzoate at concentrations of both 10 and 20 % as well as in all mixed hydrotropic solution containing these two agents. In conclusion, urea shows promising data as a potential additive with SC to achieve higher solubility and bioavailability of the compound.